Selective Reporting of Placebo Tests in Top Economics Journals - Anna Dreber; Magnus Johannesson; Yifan Yang (Institute for Replication (I4R), 2023)
Placebo tests, where a null result is used to support the validity of the research design, is common in economics. Such tests provide an incentive to underreport statistically significant tests, a form of reversed p-hacking. Based on a pre-registered analysis plan, we test for such underreporting in all papers meeting our inclusion criteria (n=377) published in 11 top economics journals between 2009-2021. If the null hypothesis is true in all tests, 2.5% of them should be statistically significant at the 5% level with an effect in the same direction as the main test (and 5% in total). The actual fraction of statistically significant placebo tests with an effect in the same direction is 1.29% (95% CI [0.83, 1.63]), and the overall fraction of statistically significant placebo tests is 3.10% (95% CI [2.2, 4.0]). Our results provide strong evidence of selective underreporting of statistically significant placebo tests in top economics journals.
Keywords: 330